Compressed Earth Blocks in sustainable construction: A critical review of technical properties and applications - Nguyen, Tuan Anh (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
This critical review examines recent research on Compressed Earth Blocks (CEBs) to evaluate their potential in sustainable construction. Through analysis of studies on mechanical, thermal, and environmental properties, this paper identifies that compressive strength, thermal conductivity, and environmental performance vary significantly across different CEB formulations. Studies suggest CEBs generally demonstrate a lower environmental impact compared to conventional building materials, with reduced CO2 emissions and energy consumption. Additives such as cement, lime, natural fibers, and agricultural by-products reportedly improve technical properties, though performance remains generally below that of conventional materials like fired bricks and concrete. Alternative stabilizers, including natural gums, pozzolanic materials, and geopolymers, show promise for reducing reliance on cement while maintaining adequate performance. This review identifies significant research gaps, including limited data on long-term durability, incomplete life cycle assessments, and lack of standardization. These findings provide a foundation for researchers and practitioners working in sustainable construction, while acknowledging the current limitations that must be addressed before wider adoption.